2021
DOI: 10.3389/fonc.2021.611580
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-seq Reveals Characteristics of Malignant Cells and Immune Microenvironment in Subcutaneous Panniculitis-Like T-Cell Lymphoma

Abstract: BackgroundSubcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a malignant primary T-cell lymphoma that is challenging to distinguish from autoimmune disorders and reactive panniculitides. Delay in diagnosis and a high misdiagnosis rate affect the prognosis and survival of patients. The difficulty of diagnosis is mainly due to an incomplete understanding of disease pathogenesis.MethodsWe performed single-cell RNA sequencing of matched subcutaneous lesion tissue, peripheral blood, and bone marrow from a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…RUNX1 and GATA2 are essential for normal megakaryopoiesis ( 7 ). ELF1 (E74-like ETS transcription factor 1) is one the top 10 transcriptional factors (TFs) among MKs ( 5 ) in yolk sac (YS), which warrants further research. Experiments showed that platelet factor 4 ( PF4 ), an inhibitor of megakaryopoiesis ( 8 ), is regulated by ELF1 ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RUNX1 and GATA2 are essential for normal megakaryopoiesis ( 7 ). ELF1 (E74-like ETS transcription factor 1) is one the top 10 transcriptional factors (TFs) among MKs ( 5 ) in yolk sac (YS), which warrants further research. Experiments showed that platelet factor 4 ( PF4 ), an inhibitor of megakaryopoiesis ( 8 ), is regulated by ELF1 ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies were transcriptional profiling of AMKL, which undermined the heterogeneity of tumors. Recently, single-cell RNA sequencing (scRNA-seq) was performed in numerous cancers to study the intratumoral heterogeneity, developing trajectory, and immune microenvironment ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, targeting of the TIM-4-AMPKa1 interaction would be effective to augment antitumor immunity and improve cancer chemotherapy ( 20 ). Recently, it has been reported that TIM-4 is specifically expressed in subcutaneous panniculitis T-cell lymphoma (SPTCL) malignant cells, indicating that TIM-4 may be a potential novel marker for SPTCL ( 34 ).Indeed, TIM-4 has been reported as a potential target for cancer diagnosis and therapy ( 35 ).Besides, TIM-4 is detected in several kinds of cancer including glioma, colorectal cancer, parapharyngeal liposarcoma, and so on. Consistently, our studies show that the expression of TIM-4 in NSCLC is significantly higher than adjacent tissues and increased expression of TIM-4 promotes metastasis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous panniculitis-like T-cell lymphoma (SPTcL) is a malignant primary T-cell lymphoma. delay in diagnosis and a high misdiagnosis rate affect the prognosis and survival of patients (83). Through single-cell RNA sequencing, TIM-4 was identified as a potential novel marker for SPTCL, which was specifically differentially expressed in the SPTCL cells.…”
Section: Regulatory Role Of Tim-4 In the Occurrence And Development O...mentioning
confidence: 99%
“…Through single-cell RNA sequencing, TIM-4 was identified as a potential novel marker for SPTCL, which was specifically differentially expressed in the SPTCL cells. This offers insight into the heterogeneity of SPTcL (83). TIM-4 is involved in a variety of cellular biological functions of tumor cells.…”
Section: Regulatory Role Of Tim-4 In the Occurrence And Development O...mentioning
confidence: 99%